Failure of the Anticoagulant Therapy and Psychological Distress: Still Far From a Bridge - Galli, Federica; Borghi, Lidia; Faioni, Elena; Cavicchioli, Marco; Ferrari Losi, Jessica; Vegni, Elena (Frontiers in Psychology, 2018)
Background. The procoagulant stress response reflects part of a beneficial adaptation of the organism to environmental threats, but a protracted procoagulant state generates a thrombotic risk. Atrial fibrillation (AF) is the most common arrhythmia in the general population. Patients with AF have a higher risk of thromboembolic events and stroke, therefore they are treated with long term oral anti-coagulant (OAC) therapy. The aim of this study is to evaluate if there are associations between psychological factors and the value of the International Normalized Ratio (INR). Methods. Fifty-three patients (men=25; women=28; mean ag =75.04) were recruited. The sample was divided according to the recognition (or not) of the reason why the INR was subtherapeutic (< 2) and classified as "Known Reasons" (KR = 35.84%) and "Unknown Reasons" (UR= 64.15%). Psychological assessment was based on Hospital Anxiety and Depression Scale (HADS), Emotion Regulation Questionnaire (ERQ), Brief Illness Perception Questionnaire (Brief IPQ), Toronto Alexithymia Scale (TAS-20) and the Perceived Stress Scale (PSS). Results. Based on Mann-Whitney Test, no significant difference was found in the scores of anxiety, depression, stress and emotional regulation strategies. From the TAS-20 scores analysis, UR subjects are characterized by an outward-oriented thinking (U=179.0; p=0.005). The Brief IPQ scores showed that KR patients, compared to UR patients, perceived more consequences of the disease on their life (U=184; p=0.018), had more perception of symptoms (U=192.5; p=0.027), had a poorer understanding (U=191.5; p=0.035) and perceived as more threatening the disease (U=182.5; p=0.025). Conclusions. It could not be found a clear role for